Equity valuation of Zalando SE - Müller, Marc (2022)
his dissertation covers the equity valuation of the German online fashion retail company, Zalando SE. The objective of the valuation is to determine Zalando’s fair share price as of 6 th May 2021 and to provide an investment recommendation. To justify the forecasting assumptions, an overview of the firm as well as of the external environment is presented. In the valuation process two different methods are applied: The Discounted Cash Flow Model (DCF) and the Relative Valuation. Furthermore, to account for the current economic uncertainties, a sensitivity analysis on the estimated share value was conducted. Finally, the results are compared with the assessment made in the Bank of America report. Overall, this leads to a target price per share of EUR 129, which corresponds to a 51.9% upside compared to its current share price of EUR 85. My recommendation for Zalando SE is, therefore, a buy.